PERMAINAN TRADISIONAL SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN DASAR ANAK: Nofrans Eka Saputra, Yun Nina Ekawati - Nofrans Eka Saputra; Yun Nina Ekawati (Jurnal Psikologi Jambi, 2018)
INTRODUCTION Jambi Traditional Game is one of the cultural parts in Jambi. Traditional game is something (a game) that sticks to the norms and customs through generations that can provide the sense of satisfaction or pleasure for the player. Jambi traditional game is an educational game that has been existed since ancient times, hereditary or habitual, and have benefits in improving the basic skills of children. Technological development, especially modern games nowadays are beginning to diminish traditional games in Jambi Province. METHOD This research is a qualitative research with ethnography study. This study aims to identify traditional games that had been passed down through generations, to identify and describe Jambi traditional games that can be used in improving the basic skills of children, to describe the traditional game activities that are still performed by children, and finding the right way to socialize traditional Jambi games related to basic skills of children. The data were collected by using in-depth interview method, FGD, and were analyzed by using triangulation method. RESULT The results of the study showed that there were thirteen (13) traditional game designs that are appropriate to the age of early childhood, and three (3) of them required guidance from adults / parents while in the process. The basic skills developed by traditional games are kinesthetic intelligence, linguistic intelligence, logical-mathematical intelligence, visual-spatial intelligence, musical intelligence, natural intelligence, interpersonal intelligence, Intrapersonal Intelligence, Spiritual Intelligence. CONCLUSION AND RECOMMENDATION This traditional gameplay can also emerge character values ​​in children, such as religious values, nationalist, independent, gotong royong (mutual cooperation), integrity. Traditional game socialization can be done by compiling pocket books on games that can be introducted in early childhood education such as playschool and Kindergarten in the form of direct experience as well as training in making Games Tool Education/Alat Permainan Edukatif (APE) based on local culture and disseminated through the website in the form of digital books. Keywords: traditional games, children's basic skills, digital media